Antinomi Norma Perlindungan Lahan Pertanian Pangan Berkelanjutan pada Kebijakan Ekspansi Perkebunan Energi di Papua dalam Menghadapi Darurat Energi : The Antinomy of Norms Protecting Sustainable Food-Crop Agricultural Land versus Energy Plantation Expansion Policies in Papua Amidst the Energy Emergency - Relys Sandi Ariani; Si Yusuf Al Hafiz; Nanik Agustiningrum; Esa Arung Syuhada; Rizky Perdana Bayu Putra (UIN Kiai Haji Ahmad Sidiq Jember, 2026)
This study aims to analyze the antinomy of norms between the protection of Sustainable Food Agricultural Land (LP2B) and the expansion policy of energy plantations in Papua in the context of the national energy emergency. The normative legal method uses a statutory, conceptual, and case approach, through a study of regulations related to LP2B, agrarian, and energy, as well as relevant doctrines and court decisions. The results show that there is regulatory disharmony between LP2B protection norms and energy expansion plans, which causes legal uncertainty in land management. The application of principles for resolving norm conflicts such as lex superior, lex specialis, and lex posterior has not been able to resolve the conflict because it is formal in nature. More substantive and integrative legal harmonization is needed to balance the interests of food security and sustainable and equitable energy ABSTRAK Penelitian ini bertujuan untuk menganalisis antinomi norma antara perlindungan Lahan Pertanian Pangan Berkelanjutan (LP2B) dan kebijakan ekspansi perkebunan energi di Papua dalam konteks darurat energi nasional. Metode hukum normatif dengan pendekatan perundang-undangan, konseptual, dan kasus, melalui studi terhadap peraturan terkait LP2B, agraria, dan energi, serta doktrin dan putusan pengadilan yang relevan. Hasil penelitian menunjukkan bahwa terdapat disharmoni regulasi antara norma perlindungan LP2B dan rencana ekspansi energi yang menyebabkan ketidakpastian hukum dalam pengelolaan lahan. Penerapan asas penyelesaian konflik norma seperti lex superior, lex specialis, dan lex posterior belum mampu menyelesaikan konflik karena bersifat formal. Diperlukan harmonisasi hukum yang lebih substantif dan integratif untuk menyeimbangkan kepentingan ketahanan pangan dan energi berkelanjutan dan adil.